(untitled) (Research, Society and Development, 2020)
Civil construction materials have been gaining more and more demands to become more sustainable, both by science and also by the market, mainly because it is a sector that consumes a large amount of raw materials, also generating a lot of waste. The search for solutions that enable the reuse or recycling of solid waste must add practical and economical solutions that generate benefits for society and the environment. In the present study, ash from the açaí stone from the burning of products from the industry itself was incorporated into the mass of red ceramics to evaluate the best ash substitution content (in the contents of 0%, 10%, 15% and 20%) in the ceramic composition, seeking to subsidize technically and environmentally the disposal of this solid waste. The results showed that even with the incorporation of the contents of Residues from Açaí Seed - RCA, the properties of mechanical resistance, apparent porosity and absorption remained within the minimum standards. It is noteworthy that the 10% ash content as a partial substitute for red clay was the one that showed the best performance in the evaluated technological properties. It was found that the ash from the açaí core has technical and environmental viability when partially inserted, making it possible to reset the RCA through the ceramic industries, since the ash residue that was generated after burning in the kilns, can be incorporated as raw material in the ceramic products themselves.